"He Who Owns the Trifels, Owns the Reich": Nazi Medievalism and the Creation of the Volksgemeinschaft in the Palatinate. Issue 2 (23rd June 2016) - Link, Fabian; Hornburg, Mark W.
Abstract: This article analyzes the interplay between Nazi cultural politics and regional identity in the Palatinate region of Germany through the lens of the Ludwig Siebert program. Created by Bavarian Minister-President Ludwig Siebert in the early 1930s to stimulate the regional construction industry, this program involved the conservation of medieval castles and ruins in Bavaria and the Palatinate. The renovation of these monuments, which had been central to the cultural memory and identity of Pfälzers since at least the nineteenth century, proved to be effective in mobilizing the local populace for Siebert's aims and, consequently, for the goals of the Nazi regime. Because its melding of cultural politics and regional identity helped to stabilize the regime in the Palatinate during its early years, the Siebert program provides a particularly illustrative microhistorical case study of the Nazi regime's mechanisms for creating the Volksgemeinschaft in the provinces. By focusing on the Palatinate town of Annweiler, which sits at the foot of the storied Trifels castle, a favored renovation project of Siebert's, this article offers a closely observed demonstration of these mechanisms at work. Abstract : Im vorliegenden Aufsatz wird am Beispiel des Ludwig-Siebert-Programmes das Zusammenspiel nationalsozialistischer Kulturpolitik und regionaler Identität in der Pfalz untersucht. Das Anfang der 1930er Jahre vom bayerischen Ministerpräsidenten Ludwig Siebert zur Stimulierung der regionalen Bauindustrie ins Leben gerufene Programm beinhaltete die Konservierung mittelalterlicher Burgen und Ruinen in Bayern und der Pfalz. Dabei erwies sich die Renovierung dieser Monumente, die für das kulturelle Gedächtnis und die kulturelle Identität der Pfälzer mindestens seit dem 19. Jahrhundert einen zentralen Stellenwert besaßen, als effektiv, um die örtliche Bevölkerung für Sieberts Ziele und folglich auch für die Ziele des Naziregimes zu mobilisieren. Da die Verschmelzung von Kulturpolitik und regionaler Identität dazu beitrug, das Regime in der Pfalz während der frühen Jahre zu stabilisieren, liefert das Siebert-Programm eine besonders anschauliche mikrohistorische Fallstudie der von den Nationalsozialisten zur Erschaffung der NS-Volksgemeinschaft in den Provinzen angewandten Mechanismen. Durch den Fokus auf die südpfälzische Kleinstadt Annweiler, die sich unterhalb der sagenumwobenen Reichsburg Trifels befindet und eines von Sieberts bevorzugten Renovierungsprojekten war, kann in diesem Aufsatz genau dargestellt werden, wie diese Mechanismen funktionierten.